EFFECTS OF PANDEMIC COVID-19 ON THE MALAYSIAN ECONOMY, FOCUSED ON FIVE IMPORTANT INDUSTRIES AND SHARIAH VIEWPOINTS - MUHAMMAD HAIQAL TAJUDEN; MUHAMMAD NABIL NORHASMY; MUHAMMAD RIZWAN NASUTION BIN MOHD IDRIS; MUHAMMAD ADHAM MOHAMAD ARES; MUHAMMAD FAIZZUWAN MUSTAFA; FUADAH JOHARI (IQTISHADUNA, 2022)
Globally, more than 4.3 million confirmed cases and more than 2,90,000 fatalities occurred due to the COVID-19 disease outbreak, which profoundly affected the entire planet. This has also fanned fears of a forthcoming economic collapse and recession. This type of event is referred to as a "black swan" because it adds unexpected and unique aspects to the economic environment and has the potential to start a chain of unfavourable reactions and market disruptions. As a result of social isolation, self-isolation, and travel restrictions, there has been a drop in the labour force across all economic sectors, resulting in the loss of several jobs. In addition, due to the closing of schools, demand for commodities and manufactured goods has decreased. On the other hand, the need for medical supplies is expanding rapidly. Through the end of 2019, the five primary economic sectors generated money and employment. Early in 2020, however, these industries encountered a major economic and employment crisis due to the COVID-19 outbreak. The COVID-19 outbreak has greatly affected the economic and social conditions of the nation, particularly regarding these five core economic activities. This study's objective is to examine the effects of COVID-19 on the agriculture, manufacturing, construction, services, mining and quarrying sectors. To achieve this purpose, this study employed descriptive analysis to examine performance data encompassing 10 years (2012 - 2021). The findings indicate that the COVID-19 epidemic has a substantial and negative impact on the Malaysian economy.